2008
DOI: 10.1093/molbev/msn001
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection and Expression Divergence Following Gene Duplication in the Sunflower CYCLOIDEA Gene Family

Abstract: Members of the CYCLOIDEA (CYC)/TEOSINTE-BRANCHED1 (TB1) group of transcription factors have been implicated in the evolution of zygomorphic (i.e., bilaterally symmetric) flowers in Antirrhinum and Lotus and the loss of branching phenotype during the domestication of maize. The composite inflorescences of sunflower (Helianthus annuus L. Asteraceae) contain both zygomorphic and actinomorphic (i.e., radially symmetric) florets (rays and disks, respectively), and the cultivated sunflower has evolved an unbranched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(178 citation statements)
references
References 81 publications
8
169
1
Order By: Relevance
“…In particular, the RAY3 gene fragment was shown to be a homolog of the sunflower HaCYC2b gene and gerbera GhCYC4 and GhCYC9. While RAY3 expression was consistent with GhCYC4 and GhCYC9 (Tähtiharju et al, 2012), its expression differed from that of HaCYC2b (Tähtiharju et al, 2012;Chapman et al, 2008). Our in situ hybridization and qRT-PCR data showed that RAY3 was expressed mainly in ray florets throughout all stages (Figs.…”
Section: Interaction Among Floral Symmetry Regulatorsmentioning
confidence: 58%
See 2 more Smart Citations
“…In particular, the RAY3 gene fragment was shown to be a homolog of the sunflower HaCYC2b gene and gerbera GhCYC4 and GhCYC9. While RAY3 expression was consistent with GhCYC4 and GhCYC9 (Tähtiharju et al, 2012), its expression differed from that of HaCYC2b (Tähtiharju et al, 2012;Chapman et al, 2008). Our in situ hybridization and qRT-PCR data showed that RAY3 was expressed mainly in ray florets throughout all stages (Figs.…”
Section: Interaction Among Floral Symmetry Regulatorsmentioning
confidence: 58%
“…2 and 3A). The RAY3 sunflower homolog HaCYC2b was initially expressed in ray florets as seen here in Senecio; however, later, HaCYC2b was expressed across multiple floral and vegetative tissues including disc florets (Tähtiharju et al, 2012;Chapman et al, 2008). Instead, RAY3 expression was more similar to the sunflower paralogs, HaCYC2c and HaCYC2d, which were expressed mainly in ray florets throughout all stages.…”
Section: Interaction Among Floral Symmetry Regulatorsmentioning
confidence: 74%
See 1 more Smart Citation
“…The putative TURF-HaCYC2c peptide was 381 amino acids long with a calculated molecular mass of 43,570 Da. No nucleotide polymorphisms were detected between the CDS sequences of TURF-HaCYC2c and the HaCYC2c previously isolated in sunflower (GenBank accession number EU088370; Chapman et al 2008). However, in the HaCYC2c gene isolated from the USDA inbred line Ames 3963 , the intron is positioned before the stop codon (see Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Expression analysis suggests that gene duplication was followed by divergence in gene regulation and that the specific expression of HaCYC2c only in ray petals indicates a possible role in floral symmetry regulation. (39) In other members of the Asteraceae, however, fewer copy numbers, such as three for Gerbera hybrida and two for Senecio vulgaris, are reported (Fig. 3B).…”
Section: Molecular Network Controlling Monosymmetry Development In Anmentioning
confidence: 98%